On the evolution of carry‐over effects. Issue 12 (6th September 2019) - Moore, Michael P.; Martin, Ryan A.
Abstract: The environment experienced early in life often affects the traits that are developed after an individual has transitioned into new life stages and environments. Because the phenotypes induced by earlier environments are then screened by later ones, these 'carry‐over effects' influence fitness outcomes across the entire life cycle. While the last two decades have witnessed an explosion of studies documenting the occurrence of carry‐over effects, little attention has been given to how they adapt and diversify. To aid future research in this area, we present a framework for the evolution of carry‐over effects. Carry‐over effects can evolve in two ways. First, the expression of traits later in life may become more or less dependent on the developmental processes of earlier stages (e.g., 'adaptive decoupling'). Genetic correlations between life stages then either strengthen or weaken. Alternatively, those influential developmental processes that begin early in life may become more or less sensitive to that earlier environment. Here, plasticity changes in all the traits that share those developmental pathways across the whole life cycle. Adaptive evolution of a carry‐over effect is governed by selection on the induced phenotypes in the later stage, and also by selection on any developmentally linked traits in the earlier life stage. When these selective pressures conflict, the evolution of the carry‐over effect will be biased towards maximizing performance in the life stage with stronger selection. Because life stages often contribute unequally to total fitness, the strength of selection in any one stage depends on: (a) the relationship between the traits and the stage‐specific fitness components (e.g., juvenile survival, adult mating success), and (b) the reproductive value of the life stage. Considering the evolution of carry‐over effects reveals several intriguing features of the evolution of life histories and phenotypic plasticity more generally. For instance, carry‐over effects that manifest as maladaptive plasticity in one life stage may represent an adaptive strategy for maximizing fitness in stages with stronger selection. Additionally, adaptation to novel environments encountered early in the life cycle may be faster in the presence of carry‐over effects that influence sexually selected traits. Abstract : Despite two decades of research on carry‐over effects, little previous consideration has been given to how they adapt and diversify. Unifying theory from the study of life histories and phenotypic plasticity, the authors describe evolutionary trajectories of carry‐over effects, provide illustrative examples and offer recommendations for future work. Photo Credit: M.P Moore